Earliest amniote tracks recalibrate the timeline of tetrapod evolution - John A. Long; Grzegorz Niedźwiedzki; Jillian Garvey; Alice M. Clement; Aaron B. Camens; Craig A. Eury; John Eason; Per E. Ahlberg (Nature, 2025)
Abstract The known fossil record of crown-group amniotes begins in the late Carboniferous with the sauropsid trackmaker Notalacerta 1,2 and the sauropsid body fossil Hylonomus 1–4. The earliest body fossils of crown-group tetrapods are mid-Carboniferous, and the oldest trackways are early Carboniferous5–7. This suggests that the tetrapod crown group originated in the earliest Carboniferous (early Tournaisian), with the amniote crown group appearing in the early part of the late Carboniferous. Here we present new trackway data from Australia that challenge this widely accepted timeline. A track-bearing slab from the Snowy Plains Formation of Victoria, Taungurung Country, securely dated to the early Tournaisian8,9, shows footprints from a crown-group amniote with clawed feet, most probably a primitive sauropsid. This pushes back the likely origin of crown-group amniotes by at least 35–40 million years. We also extend the range of Notalacerta into the early Carboniferous. The Australian tracks indicate that the amniote crown-group node cannot be much younger than the Devonian/Carboniferous boundary, and that the tetrapod crown-group node must be located deep within the Devonian; an estimate based on molecular-tree branch lengths suggests an approximate age of early Frasnian for the latter. The implications for the early evolution of tetrapods are profound; all stem-tetrapod and stem-amniote lineages must have originated during the Devonian. It seems that tetrapod evolution proceeded much faster, and the Devonian tetrapod record is much less complete, than has been thought.